2014
DOI: 10.2903/j.efsa.2014.3566
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of iron compounds (E1) as feed additives for all species: ferrous sulphate heptahydrate based on a dossier submitted by Kronos International, Inc.

Abstract: Scientific Opinion on the safety and efficacy of iron compounds (E1) as feed additives for all species: ferrous sulphate heptahydrate based on a dossier submitted by Kronos International, Inc. ABSTRACTFerrous sulphate heptahydrate is safe when supplied up to a maximum iron content per kilogram complete feedingstuff of 450 mg for bovines and poultry, 500 mg for ovines, 600 mg for pets, and 750 mg for other species/categories, except horses and fish; for piglets up to one week before weaning a maximum of 250 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a. It was concluded that no concerns for consumer safety are expected when iron compounds are used up to the EU maximum authorised level in feed.…”
Section: Safety For the Consumermentioning
confidence: 99%
See 1 more Smart Citation
“…The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a. It was concluded that no concerns for consumer safety are expected when iron compounds are used up to the EU maximum authorised level in feed.…”
Section: Safety For the Consumermentioning
confidence: 99%
“…In the absence of specific studies and considering that several iron compounds are recognised as irritants to skin, eyes and mucous membranes (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a, the product should be considered as a skin, eye and respiratory irritant.…”
Section: Effects On the Eyes And Skinmentioning
confidence: 99%
“…The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013a, 2014a,b, 2015, 2016a. The safety for consumers of foods derived from animals whose diets were supplemented with iron compounds, including chelate of amino acids, has been reviewed and assessed by the FEEDAP Panel (EFSA FEEDAP Panel, 2013a, 2014a,b, 2015, 2016a.…”
Section: Safety For the Consumermentioning
confidence: 99%
“…The opinion is based on data provided by a company involved in the production/distribution of ferric oxide and publicly available literature. In particular, the Opinion on the re-evaluation of iron oxides and hydroxides (E 172) as food additives (EFSA ANS Panel, 2015) and the Opinions on ironbased feed additives (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a) and on iron oxide black, red and yellow as colourings in feed (EFSA FEEDAP Panel, 2016b) were considered.…”
Section: Assessmentmentioning
confidence: 99%
“…The FEEDAP Panel expresses in the current opinion its concern on the safety of ferric oxide as compound of trace element as long as such a genotoxicity study is not provided. (EFSA FEEDAP Panel, 2013, 2014a,b, 2015, 2016a) that they are safe when supplied up to a maximum iron content per kilogram complete feedingstuff of 450 mg for bovines and poultry, 500 mg for ovines, 600 mg for pets, and 750 mg for other species/categories, except horses and fish; for piglets up to 1 week before weaning a daily maximum dose of 250 mg Fe is considered safe. Because of insufficient data, the FEEDAP Panel was not in a position to derive a maximum safe iron concentration in feed for horses or fish.…”
Section: Toxicological Studiesmentioning
confidence: 99%